1981
DOI: 10.1007/bf00435850
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of disordered renal excretion of xanthurenic acid in depressive patients

Abstract: Xanthurenic acid is a metabolite of L-tryptophanicotinic acid ribonucleotide biosynthesis. The excretion of xanthurenic acid from urine 24 h after ingestion of 5 g L-tryptophan is increased in depressive patients, and 17-hydroxycorticosteroids are considered of primary importance to this disorder. However, in this study, the excretion of xanthurenic acid and 17-hydroxycorticosteroids did not correlate with the scores of the Raskin depression scale, Hamilton depression scale, Zung depression scale, or the Zung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Discussion of these differences is rather difficult because Hilgerson (1984) did not mention either the statistical methods used or the composition of his group of psychiatric controls. We did not find differences in XA excretion between major and minor depression, which is in accordance with Hoes (1979), who established no differences in XA excretion between patients suffering from melancholia and those with an adaptation disorder with depressed mood (included in our group of minor depression).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Discussion of these differences is rather difficult because Hilgerson (1984) did not mention either the statistical methods used or the composition of his group of psychiatric controls. We did not find differences in XA excretion between major and minor depression, which is in accordance with Hoes (1979), who established no differences in XA excretion between patients suffering from melancholia and those with an adaptation disorder with depressed mood (included in our group of minor depression).…”
Section: Discussionsupporting
confidence: 92%
“…The renal excretion of xanthurenic acid (XA) following L-tryptophan (L-TRP) loading has been subject to several investigations in the field of depression (Hoes, 1979;Hilgersom, 1984;Maes et al, 1986). Xanthurenic acid is a secondary product of the conversion of L-TRP into nicotinamide.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Baran et al [30] previously observed that a significant increase in Kyna production in the putamen and caudate nucleus of AD patients was associated with an elevated kynurenine metabolism. Xantha production via the IDO-1 pathway is higher in depressed patients than controls [31] and plays a role in apoptosis [32], as well as acting as a neuromodulator in the rat brain [33]. The production of 3-OH anthra, Anthra, and Pico in AD had not previously been studied in sufficient detail.…”
Section: Resultsmentioning
confidence: 99%
“…This is important as kynurenine and quinolinic acid (QA) possess anxiogenic effects. Similarly, higher levels of kynurenine and excreted xanthurenic acid (XA) were found to be positively correlated to levels of anxiety [88,89]. Lapin et al (1996) [90] found that QA reduced the duration of social interaction, as well as grooming behavior, in mice and is therefore inferred to have anxiogenic effects.…”
Section: Sex Anxiety and The Trycat Pathwaymentioning
confidence: 99%